Mycobacterium tuberculosis Whole Genome Sequences From Southern India Suggest Novel Resistance Mechanisms and the Need for Region-Specific Diagnostics. (12th May 2017) - Manson, Abigail L.; Abeel, Thomas; Galagan, James E.; Sundaramurthi, Jagadish Chandrabose; Salazar, Alex; Gehrmann, Thies; Shanmugam, Siva Kumar; Palaniyandi, Kannan; Narayanan, Sujatha; Swaminathan, Soumya; Earl, Ashlee M.
Key points: By sequencing 223 M. tuberculosis strains from Southern India, we expanded the studied genetic diversity of lineages 1 and 3. We observed local transmission of strains; unexplained resistance; potential novel resistance mutations; and that isoniazid resistance was gained first. Abstract: Background: India is home to 25% of all tuberculosis cases and the second highest number of multidrug resistant cases worldwide. However, little is known about the genetic diversity and resistance determinants of Indian Mycobacterium tuberculosis, particularly for the primary lineages found in India, lineages 1 and 3. Methods: We whole genome sequenced 223 randomly selected M. tuberculosis strains from 196 patients within the Tiruvallur and Madurai districts of Tamil Nadu in Southern India. Using comparative genomics, we examined genetic diversity, transmission patterns, and evolution of resistance. Results: Genomic analyses revealed (1) prevalence of strains from lineages 1 and 3, (2) recent transmission of strains among patients from the same treatment centers, (3) emergence of drug resistance within patients over time, (4) resistance gained in an order typical of strains from different lineages and geographies, (5) underperformance of known resistance-conferring mutations to explain phenotypic resistance in Indian strains relative to studies focused on other geographies, and (6) the possibility that resistance arose through mutations not previously implicated in resistance, or through infections with multiple strains that confound genotype-based prediction of resistance. Conclusions: In addition to substantially expanding the genomic perspectives of lineages 1 and 3, sequencing and analysis of M. tuberculosis whole genomes from Southern India highlight challenges of infection control and rapid diagnosis of resistant tuberculosis using current technologies. Further studies are needed to fully explore the complement of diversity and resistance determinants within endemic M. tuberculosis populations.